2005
DOI: 10.1590/s0004-282x2005000600029
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização clínica e imunoistoquímica dos adenomas clinicamente não-funcionantes de hipófise: clinical features and immunohistochemistry

Abstract: RESUMO -Adenomas clinicamente não-funcionantes de hipófise, não produzem clínica de hipersecreção h o rmonal. Por esse motivo, seus sinais e sintomas dependem de seu efeito de massa no sistema nerv o s o central. A sua etiopatogenia é complexa com vários fatores provavelmente influenciando seu desenvolvimento como os hormônios hipotalâmicos (GHRH), fatores de crescimento (FGF), fatores de pro l i f e r a ç ã o (PCNA, e KI-67), proteína P53 e proto-oncogene c-erb-B2. Objetivos 1) D e t e rminar as característic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, its use in pituitary tumors is still questionable due to heterogeneity of studies, with lack of technical standardization, and the use of semiquantitative methods [35, 36]. In our series, the Ki-67 cutoff was established when positivity was found in ≥ 10% (2+) of cells, according to local standards [14, 15]. Some authors suggested that high immunostaining of Ki-67 could predict aggressive tumor behavior and distinguish invasive from noninvasive adenomas with high sensitivity and specificity [35].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, its use in pituitary tumors is still questionable due to heterogeneity of studies, with lack of technical standardization, and the use of semiquantitative methods [35, 36]. In our series, the Ki-67 cutoff was established when positivity was found in ≥ 10% (2+) of cells, according to local standards [14, 15]. Some authors suggested that high immunostaining of Ki-67 could predict aggressive tumor behavior and distinguish invasive from noninvasive adenomas with high sensitivity and specificity [35].…”
Section: Discussionmentioning
confidence: 99%
“…An immunohistochemistry analysis of the samples was previously performed at the Pathology Unit of the University Hospital of Brasilia, and the preliminary results were published [14, 15]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations